PENINGKATAN KETERAMPILAN IBU-IBU RUMAH TANGGA DALAM PEMBUATAN SALE PISANG DENGAN TEKNOLOGI PENGERING BIOMASSADI DESA PAKEMITAN,KEC. CIKATOMAS, KAB. TASIKMALAYA - Aripin; Sutisna; Muhammad Aris Risnandar (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The average banana production in Pakemitan Village is 9.2 tons/year. The jackfruit and ambon bananas dominate nearly 63.84% of the total banana production in Pakemitan Village. When the number of harvests increases, jackfruit and ambon bananas were not sold in the market. With abundant and cheap bananas, and unhygienic drying of sale bananas using sunlight, it is necessary to encourage housewives to convert bananas into sale bananas and drying them with biomass drying technology. The training implementation method starts from program socialization, theoretical training on making banana sale, preparation of tools and materials, and field practice of making banana sale and drying it with biomass dryer. The housewives who attended the training were 15 people. Housewives are informed about the procedure and practice of making banana sale and the process of drying banana sale. The results of the evaluation showed that over 80% of housewives were categorized as skilled participants in making banana sale and using biomass dryers. The results show that there is an increase in insight and knowledge of making banana sale using a biomass dryer, so participants can make banana sale independently.